Synthesized Hybrid Cnt Polymer Composite In Reducing Emi Pollution At Gigahertz Frequency Range - Fadzidah Binti Mohd Idris; Mohd Shamsul Ezzad Shafie; Siti Nor Ain Rusly; Hatika Kaco; Siti Munirah Mohd; Nurhidaya Mohamad Jan; Abubakar Yakubu (Semarak Ilmu Publishing, 2024)
Semarak International Journal of Nanotechnology, Volume 1 Issue 1 Page (1–12)